WORK PERFORMANCE THROUGH EDUCATION LEVEL, AGE, AND EXPERIENCE AT UNIVERSITAS PGRI ADI BUANA SURABAYA - Arianto, Bisma; Asj’ari, Fachrudy (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
The competence of educational personnel is one of the success factors for the sustainability of the Teacher Training Institute which must be regulated dynamically. One of the fundamental things related to the performance of educational personnel is the competence they have. This competence is influenced by many factors including education level, age, and experiences. The three of them are components that affect the productivity and performance of the educational personnel in the Universitas PGRI Adi Buana Surabaya. The education level data, age, and experiences were collected through the documentation, while the performance of education personnel was collected through a questionnaire. The hypothesis was tested using a quantitative analysis using statistical test tools. The results of this study indicate that (1) the education level has a significant effect on the performance of educational personnel by 10.1%; (2) age does not have a significant effect on teaching staff performance; (3) experience has a significant effect on the performance of educational personnel by 11.4%; and (4) education level, age, and experience have a significant simultaneous effect on the performance of the educational personnel at the Universitas PGRI Adi Buana Surabaya by 21.8%. This is indicated by the sig value <.05 for the education level, age, and experience.